Pendampingan Hukum Penyalahgunaan Media Sosial di SMAN 2 Kota Serang - Setiadi, Wicipto; Harefa, Beniharmoni; suyanto, heru; Indrirarosa, Martina (Center of Community Service (PPM), Institute for Research and Community Services (LP2M) UI, 2021)
The development of information and technology, has a positive impact on human life, but on the other, it will have a negative impact. The misuse of social media, especially in the school, is an important thing to pay attention to. This paper aims to provide understanding and legal assistance in order to avoid misuse of social media. The first step taken was to provide socialization and enlightenment to the students and the school, especially SMAN 2 Kota Serang about the dangers of misuse of social media. Understanding and enlightening students about the dangers of misuse of social media is an effort to prevent the occurrence of misuse of social media, especially in the school. The results and impact of the implementation of program can be seen in the understanding of students and schools regarding the dangers of misuse of social media. Keywords: legal protection, UU ITE, studentAbstrak:Perkembangan informasi dan teknologi disatu sisi memberikan dampak positif bagi kehidupan manusia, namun disisi lain akan memberikan dampak negatif. Penyalahgunaan media sosial khususnya dilingkungan sekolah menjadi hal penting untuk diperhatikan. Tulisan ini bertujuan untuk memberikan pemahaman dan pendampingan hukum guna menghindari penyalahgunaan media sosial. Langkah pertama yang dilakukan adalah memberikan sosialisasi dan pencerahan kepada para siswa dan pihak sekolah khususnya SMAN 2 Kota Serang akan bahaya penyalahgunaan media sosial. Pemahaman dan pencerahan kepada para siswa akan bahaya penyalahgunaan media sosial menjadi upaya pencegahan (preventif) terjadinya penyalahgunaan media sosial khususnya di lingkungan sekolah. Hasil dan dampak pelaksanaan kegiatan terlihat pada pemahaman siswa dan pihak sekolah pada bahaya penyalahgunaan media sosial. Kata kunci: perlindungan hukum, UU ITE, siswa